Evaluation of Music Learning: Role-Playing Method Using Musician in Early Children - Mastri Dihita Sagala (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2024)
This research focuses on evaluating music learning using the role-playing method at the Favore Music School in Bandung. The class consists of young children aged 3-4 years who have an interest in practicing music. The Alfred Music curriculum is used as a reference in implementing music learning. The purpose of the study was to see how the role-playing method contained in the curriculum can increase the interest and talent of early childhood in playing music, through the musician figures presented in the method. Data was obtained through observation, interviews, documentation and literature study. The research results show that learning music using the role-playing method can not only improve musical abilities in young children, but also language skills and processing feelings, both emotional, self-confidence and social. In the musical context, the role-playing method using musician characters can motivate children to practice diligently to become proficient in playing music, so that they have the desire to be like the characters they idolize. The implications of this study can be a reference in developing a music learning curriculum. This curriculum was born from New York so that the storyline uses an approach to habits and environmental culture that is common in Western countries. Therefore, it is a good reference for innovating the curriculum by involving regional languages and even prominent musicians in Indonesia and instilling Indonesian cultural values.